The scarlet thread eaudiobook - Rivers, Francine (Recorded Books Inc., 2012)
New York Times best-selling author Francine Rivers has won such prestigious honors as the Christy Award for Inspirational Historical Fiction and the ECPA Gold Medallion. In The Scarlet Thread, a woman learns to cope with life's challenges by looking to the past. Sierra and her family move to Los Angeles when her husband lands a new job — but big-city life brings many problems. Soon, Sierra finds herself watching helplessly as her family disintegrates. Then she discovers an ancestor's journal — and slowly learns to put her trust in God.